Implementasi Wakaf Tunai Dalam Perspektif Hukum Islam (Studi Kasus di KUA Tarogong Kidul) - Munir, Ridwan; Nurpadilah, Ulfah (STAI Al Musaddadiyah Garut, 2022)
One form of worship related to wealth with the aim of bringing each individual closer to the Creator is the practice of endowment (wakaf). However, currently under discussion is the topic of cash endowment (wakaf tunai). The problem formulation in this research is: How is the Implementation of Cash Endowment in the Perspective of Islamic Law at the Office of Religious Affairs in Tarogong Kidul? The aim of this research is to analyze how Cash Endowment is implemented in the Perspective of Islamic Law at the Office of Religious Affairs in Tarogong Kidul. The research method used in this study is field research and a qualitative approach. Data collection techniques involve interviews, and data analysis is conducted by organizing the collected data into logical and systematic descriptions, followed by deductive conclusions. The results of the research lead to the conclusion that Endowments at the Office of Religious Affairs in Tarogong Kidul comply with the conditions and pillars of endowment, but the implementation of cash endowment has not been feasible because most endowment contributors do not fully understand cash endowment, highlighting the need for public awareness and education regarding endowment practices. Keywords: Cash Endowment, Perspective of Islamic Law